The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1302/0301-620x.105b6.bjj-2022-0931.r1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a revision arthroplasty network on patient outcomes

Abstract: AimsRevision total knee arthroplasty (rTKA) and revision total hip arthroplasty (rTHA) are complex procedures with higher rates of re-revision, complications, and mortality compared to primary TKA and THA. We report the effects of the establishment of a revision arthroplasty network (the East Midlands Specialist Orthopaedic Network; EMSON) on outcomes of rTKA and rTHA.MethodsThe revision arthroplasty network was established in January 2015 and covered five hospitals in the Nottinghamshire and Lincolnshire area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…A team of authors from Nottingham (UK) examined the outcome of the East Midlands Specialist Orthopaedic Network, a network covering Nottinghamshire and Lincolnshire, comparing their results pre- and post-network (starting January 2015), and also used Hospital Episodes Statistics data to compare their results to the rest of England. 4 Their primary outcome was re-revision within one year, and secondary outcomes included re-revision rates at two years, complication rates at one and two years, and emergency readmission within 90 days. Using comparative interrupted time series analysis, the authors demonstrated an immediate significant improvement in one- and two-year re-revision rates for rTKA, but not for rTHA.…”
Section: The Impact Of a Revision Arthroplasty Network On Patient Out...mentioning
confidence: 99%
“…A team of authors from Nottingham (UK) examined the outcome of the East Midlands Specialist Orthopaedic Network, a network covering Nottinghamshire and Lincolnshire, comparing their results pre- and post-network (starting January 2015), and also used Hospital Episodes Statistics data to compare their results to the rest of England. 4 Their primary outcome was re-revision within one year, and secondary outcomes included re-revision rates at two years, complication rates at one and two years, and emergency readmission within 90 days. Using comparative interrupted time series analysis, the authors demonstrated an immediate significant improvement in one- and two-year re-revision rates for rTKA, but not for rTHA.…”
Section: The Impact Of a Revision Arthroplasty Network On Patient Out...mentioning
confidence: 99%